COMPARATIVE STUDY ON EFFECT OF ALUMINIUM CHLORIDE AND ALUMINIUM HYDROXIDE ON SERUM BIOCHEMICAL PARAMETERS IN WISTAR ALBINO RATS - SILPA NARAYANAN (International Journal of Pharma and Bio Sciences, 2014)
Aluminium is one of the trace elements with a moderate toxic effect on living organisms. This study is to assess the influence of aluminium chloride and aluminium hydroxide intake on biochemical parameters in experimental animals for 21 days. Administration of aluminium chloride and aluminium hydroxide at a dose of 300mg/kg of body weight significantly elevates blood serum urea and creatinine concentration but no change in serum Protein level.